Strategi Pemberian Kredit dalam Pencegahan Kredit Macet pada PT. BPR Bank Jombang Perseroda - Silvy Rachmawati; Anita Akhirruddin (VISA: Journal of Vision and Ideas, 2024)
This research aims to develop strategies regarding good credit granting procedures to reduce the occurrence of problem loans at PT. BPR Bank Jombang Perseroda. So this research can be a reference in managing bank management and for consideration in decisions for each activity, especially those related to the distribution of funds. The research method uses documentation, interviews and literature study. The data source in this research is primary data in the form of interviews with several PT employees. BPR Bank Jombang Perseroda, as well as secondary data in the form of annual reports and collectibility at PT. BPR Bank Jombang Perseroda. This type of research is descriptive with a qualitative approach. Data analysis uses the Miles and Huberman model, namely data reduction, data display, and drawing conclusions and verification. Research results: In the discussion that has been explained, the credit distribution activities of PT. BPR Bank Jombang Perseroda goes through several stages and procedures, namely starting with a credit application by filling out a credit application form according to the type of credit being applied for, carrying out a credit feasibility analysis, then deciding whether to approve the credit application or not according to the calculations made, until the disbursement process. There are several factors that are analyzed by financial institutions before approving a credit application, including business prospects, debtor performance and ability to pay. The benchmark for granting credit or the technique for analyzing the character of prospective debtors carried out by Bank Jombang is through the BI Checking process. Apart from that, the things that the bank must consider when granting credit are, Personality, Party, Purpose, Prospect, Payment, Profitability , and Protection.